2013
DOI: 10.1016/j.physio.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Trunk muscle activity while lifting objects of unexpected weight

Abstract: Trunk muscles may not be able to function appropriately when individuals lift an object that is much heavier than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(10 reference statements)
3
9
0
2
Order By: Relevance
“…The results showed that the preferred walking speed did not present significant differences between the teams, but this was not seen at the literature review that reports lower preferred speed and maximum walking in the elderly population [10]. This can occur due to the functional adaptation [11] that has as characteristic, for example, shorter step length and higher step width [1]. The findings corroborate the literature because the participants of this study are young; with this, the pain may not have interfered with the walking speed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results showed that the preferred walking speed did not present significant differences between the teams, but this was not seen at the literature review that reports lower preferred speed and maximum walking in the elderly population [10]. This can occur due to the functional adaptation [11] that has as characteristic, for example, shorter step length and higher step width [1]. The findings corroborate the literature because the participants of this study are young; with this, the pain may not have interfered with the walking speed.…”
Section: Discussionmentioning
confidence: 86%
“…The lumbar pain [LP] is the main physical complaint reported by the active population [1] and mainly in voluntary activities, in which 80% of them evolve with symptom remission, while 20% become chronic [2]. The high incidence of LP in the population results in an increase in health expenses and longer work leave time [3].…”
Section: Introductionmentioning
confidence: 99%
“…Por ser uma modalidade onde se trabalha com sobrecargas, uma postura incorreta, durante a realização dos exercícios, pode trazer graves consequências para a coluna lombar. Para Watanabe et al, 9 os músculos do tronco podem não ser capazes de funcionar adequadamente quando os indivíduos levantam um objeto que é muito mais pesado do que o esperado para seu corpo.…”
Section: Resultsunclassified
“…Em torno de 70 a 80% da população apresentarão dor nas costas em algum momento da vida 1 e a região lombar é o principal local de acometimento 2 . A dor lombar (DL) é uma disfunção musculoesquelética, caracterizada por dor, desconforto ou aumento da rigidez da região entre último arco costal até a prega glútea 3,4 , qualificada como crônica quando superior a 12 semanas 3 .…”
Section: Introductionunclassified